Manuscripts Of The Holy Qur'an Copied In India (On The Example Of The Reigns Of Babur, Humayun And Akbar) - Hamidillo Lutfillaev (Frontline Social Sciences and History Journal, 2025)
This article presents a comprehensive study of the manuscripts of the Holy Quran copied in India during the Babur (Mughal) dynasty (1526–1858), analyzing them through historical, artistic, and aesthetic dimensions. Special attention is given to the Qurans produced during the reigns of Zahiriddin Muhammad Babur, Nasiruddin Humayun, and Jalaluddin Akbar, whose periods marked the foundation, consolidation, and cultural flourishing of the Mughal Empire. The article explores the development of manuscript-writing traditions, the evolution of calligraphic schools, and the introduction of various scripts such as suls, naskh, and nastaliq under royal patronage. In addition, the research highlights the decorative techniques applied in manuscript illumination, including the use of gold and lapis pigments, floral arabesques, and geometric patterns reflecting the synthesis of Persian, Central Asian, and Indian artistic elements. The role of royal ateliers (kitabkhana) in promoting refined calligraphy and miniature art is examined as a major factor in shaping the aesthetic identity of Qurans of this era. The article also traces the movement and preservation of these manuscripts over time, noting their dispersion across major libraries and museum collections in London, Delhi, Istanbul, and Tashkent. Through a comparative analysis of stylistic and paleographic features, the study provides new insights into how the Baburid intellectual and cultural environment influenced the spiritual visuality of Quranic manuscripts. By documenting their current condition and conservation practices, the paper underscores the importance of these works as invaluable witnesses of Islamic art and intercultural dialogue between East and South Asia.